NOTA SOBRE A OCORRÊNCIA DE Eupalea reinhardti Crotch. (COLEOPTERA, COCCINELLIDAE) ATACANDO Psylla sp. (HOMOPTERA, PSYLLIDAE) EM SIBIPIRUNA (Caesalpinia pelthophoroides Benth.) - Fraga, Alexandre Isaac Akerman; Berti Filho, Evoneo; Ciociola, Américo Iorio (REVISTA DE AGRICULTURA, 2015)
NOTA SOBRE A OCORRÊNCIA DE Eupalea reinhardti Crotch. (COLEOPTERA, COCCINELLIDAE) ATACANDO Psylla sp. (HOMOPTERA, PSYLLIDAE) EM SIBIPIRUNA (Caesalpinia pelthophoroides Benth.)